Understanding of the Interaction between Clearance Leakage Flow and Main Passage Flow in a VGT Turbine. (February 2015) - Zhao, Ben; Yang, Ce; Hu, Liangjun; Sun, Harold; Yi, James; Eric, Curtis; Shi, Xin; Engeda, Abraham
The clearance flow between the nozzle and endwall in a variable geometry turbine (VGT) has been numerically investigated to understand the clearance effect on the VGT performance and internal flow. It was found that the flow rate through turbine increases but the turbine efficiency decreases with height of clearance. Detailed flow field analyses indicated that most of the efficiency loss resulting from the leakage flow occurs at the upstream of the rotor area, that is, in the nozzle endwall clearance and between the nozzle vanes. There are two main mechanisms associated with this efficiency loss. One is due to the formation of the local vortex flow structure between the clearance flow and the main flow. The other is due to the impact of the clearance flow on the main flow after the nozzle throat. This impact reduces the span of shockwave with increased shockwave magnitude by changing the trajectory of the main flow.